Oral carriage of Staphylococcus aureus in people with different body mass index - Roshna Mohamed Qadir; Mahde Saleh Assafi (Universidad de Concepción., 2021)
Background: The association between obesity and the oral microbiome has received great attention. Objective: This study aimed to determine the association of oral Staphylococcus aureus with different body mass index people. Material and Methods: A total of 155 saliva samples were collected. The individuals were grouped into three categories according to their BMI, normal weight, overweight and obese individuals. A loopful of saliva sample was cultured and incubated at 37 °C for 24. Staphylococcus aureus isolates were diagnosed by colony characteristics, morphology, and biochemical tests. Results: The oral carriage rate of Staphylococcus aureus was 61.3% (65.1% females and 56.5% males). The Staphylococcus aureus rate was 68% in married and 60% in single people. The differences of oral carriage rates of Staphylococcus aureus in obese (73.6%) and overweight (85.4%) populations was statistically significant (p<0.0001) compared to the rate in normal weight group (34%). Among males, the highest oral carriage rate of Staphylococcus aureus was in overweight individuals (82.6%). Likewise, in females, the highest rate of salivary Staphylococcus aureus was among the overweight group (88.9%). Regarding marital status, in single people, the differences of Staphylococcus aureus in obese (p=0.0003) and overweight (p<0.0001) people was significantly compared to normal weight people. But, in married people, the differences in Staphylococcus aureus rates among all groups were statistically not significant (p=0.0935). Conclusion: Staphylococcus aureus was significantly related to overweight and obese individuals. The human oral Staphylococcus aureus may play a key role in the manifestation of obesity. The oral microbiota could provide a new target for improving the physical well being of humans.